Determinants of Generation Z’s Investment Intentions in Green Sukuk as Sustainable Investments - Amirul Althony Nazuha; Farida Rahmawati Rahmawati (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study examines the factors influencing Generation Z’s intention to invest in green sukuk by extending the pro-environmental planned behavior model with financial literacy and risk behavior variables. Using a quantitative approach and SEM-PLS analysis on 383 Generation Z respondents, the findings reveal that environmental concern and perceived authority support significantly influence attitude, subjective norm, and perceived behavioral control. Furthermore, attitude, subjective norm, perceived behavioral control, and financial literacy positively affect investment intention, while risk behavior has no significant effect. The study highlights the importance of financial literacy, institutional support, and investment accessibility in promoting sustainable investment participation among Generation Z.